Theoretical Model of Language Faculty Lecturer Performance Improvement and Unimed Arts (Study of the Influence of Organizational Culture, Work Motivation, and Job Satisfaction on Lecturer Performance FBS Unimed) - Syamsul Arif; Azhar Umar; TR Pangaribuan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to find: (1) a theoretical model of performance improvement Lecturer at the Faculty of Arts, Unimedwhich is built based on the associative causal relationship between endogenous variables and exogenous variables, (2) knowing the positive direct effects: (a) organizational culture on work motivationLecturer at FBS Unimed. (b) organizational culture on job satisfaction of Unimed FBS lecturers, (c) organizational culture on the performance of FBS Unimed lecturers (d) work motivation on the performance of Unimed FBS lecturers; (e) job satisfaction on the performance of Unimed FBS lecturers. The study population was 174 FBS Unimed lecturers, a sample of 100 people selected by means of proportional random sampling. The research instrument was a closed questionnaire with four scales. The research data were processed and analyzed using descriptive statistics and differential statistics, namely path analysis. Path analysis begins with a test requirements analysis including normality test and linearity test.X1) has a positive direct effect of 50.69% on Work Motivation (X2) lecturers of FBS Unimed as well as Organizational Culture (X1) a positive direct effect of 28.83% on Job Satisfaction (X3) lecturer at FBS Unimed, Organizational Culture (X1) also has a positive effect of 22.02% on lecturer performance (X4) FBS Unimed, and Work Motivation (X2) Has a positive direct effect of 26.22% on lecturer performance (X4) FBS Unimed and Job Satisfaction (X3) Directly positive effect of 17.75% on lecturer performance (X4) FBS Unimed.